Embodied Resistance to Persuasion in Advertising - Lewinski, Peter; Fransen, Marieke L.; Tan, Ed S. (Frontiers in Psychology, 2016)
From the literature on resistance to persuasion in advertising, much is known about how people can resist advertising by adopting resistance strategies, such as avoidance, counter-arguing and selective attention (e.g., Fransen, Verlegh, Kirmani, & Smit, 2015a). However, the role of emotion regulation and bodily expression in resisting persuasion is so far underexplored. This is a surprising observation if one considers that at least 40% of advertisements use positive emotions (i.e., happiness) to persuade people to like the ad, brand, and product (Weinberger et al., 1995). In this article we present a framework in which we apply previous knowledge and theories on emotion regulation and embodiment to the process of resistance to persuasion. In doing so, we specifically address the role of facial expression in the course of resistance. Based on the literature and findings largely established in our own research, we propose that people can resist persuasion by controlling their facial expression of emotion when exposed to an advertisement. Controlling the expression of emotions elicited by an ad (for example refusing to smile) might be a fruitful way to resist the ad’s persuasive potential. Moreover, we argue that co-viewers can affect embodied resistance to persuasion. Showing the viability of embodied resistance to persuasion is relevant in view of the fact that ads trying to persuade us by addressing our positive emotions are ubiquitous. Embodied resistance might help people to cope with these induced positive emotions in order to resist advertisements and might therefore work as a novel and effective strategy to resist persuasion.